THE MOST IMPORTANT QUESTIONS IN IR NOW ARE QUESTIONS TRADITIONALLY ASSOCIATED WITH COMPARATIVE POLITICS - S. D. Krasner (MGIMO University Press, 2019)
Stephen Krasner took part in the 8th Congress of Russian Political Science Association in Moscow (December 8-9, 2018) devoted to issues of development policy, state and world order. On the margins of the Congress he was so kind to give an interview to the managing editor of our Journal, Maxim Kharkevich.